(untitled) (Journal of Fatima Jinnah Medical University, 2018)
The term asphyxia is used to describe a condition in which the supply of oxygen at the level of mouth, nose, neck or chest externally or to blood and body tissues internally is reduced by any interference with respiration. A retrospective study was conducted in Forensic Medicine and Toxicology Department of King Edward Medical University, Lahore from January 2012 to December 2013.The aim of the study was to determine the incidence of asphyxial deaths in Lahore. During this period, out of 1686 medico legal autopsies conducted, 67 deaths were caused by violent asphyxia having incidence of 3.98%. There were 37 males (55.2%) and 30 females (44.8%). Highest incidence was seen in age group 21-30 years (41.8%). Male predominance was seen in all asphyxial deaths except strangulation. Strangulation (41.8%) and hanging (35.82%) were the leading causes of asphyxia deaths. Homicidal deaths (59.7%) were most common followed by suicidal (35.82%) and accidental deaths (4.48%) respectively. A well designed comprehensive program is required to identify the causative factors and prevention of suicidal behaviors